Carbapenemase production in hospital isolates of multidrug-resistant Klebsiella pneumoniae and Escherichia coli in Serbia - Trudić, Anika Djordje; Jelesić, Zora; Mihajlović-Ukropina, Mira; Medić, Deana; Zivlak, Branka; Gusman, Vera; Djilas, Milan (Vojnosanitetski pregled, 2017)
Abstract Background/Aim. Carbapenem resistance has escalated in medically important enterobacteria such as Klebsiella pneumoniae and Escherichia coli worldwide. Multidrug-resistant strains represent an important source of concern as effective therapeutic options of infections they cause are limited or none. There were no comprehensive studies considering the presence of carbapenemase production in enterobacteria in Serbia so far. The aim of the study was to determine carbapenemase production in hospital isolates of multidrug-resistant K. pneumoniae and E. coli in Serbia. Methods. Strains of K. pneumoniae and E. coli resistant to at least one carbapenem (imipenem, meropenem, ertapenem) were collected from November 2013 to May 2014. Isolates were obtained from clinical samples of patients treated in 14 hospitals in Serbia. Carbapenem resistance was confirmed using phenotypic tests and polymerase chain reaction (PCR) in National Reference Laboratory for Registration and Surveillance of Antimicrobial Resistance of Bacterial Strains in Novi Sad. Results. Of 129 collected strains, 121 (93.8%) were K. pneumoniae and 8 (6.2%) were E. coli. Seventy (54.3%) strains were obtained from urine, 26 (20.2%) from blood, 19 (14.7%) from wound secretions and 14 (10.9%) from lower respiratory tract secretions. Carbapenemase genes were detected in 58 (45%) isolates. The gene bla New Delhi-metallo-beta-lactamases (blaNDM) was found in 33 (27.3%) K. pneumoniae, bla oxacillinases-48 (blaOXA-48) in 10 (8.3%), bla K. pneumonia carbapenemase (blaKPC) in 1 (0.8%), and 7 (5.4%) strains harbored both blaOXA-48 and blaNDM. Seven E. coli harbored blaNDM gene. Conclusion. In Serbia, the most common type of carbapenemase in both multidrug-resistant K. pneumoniae and E. coli is NDM. Co-production of OXA-48 and NDM was found in K. pneumoniae. To our knowledge, KPC production was detected for the first time in Serbia.
Keywords: enterobacteriaceae; drug resistance; bacterial; carbapenems; cross infection; genome; serbia; beta lactamases